GROWING THE ROLE OF FINANCIAL AND ENVIRONMENTAL INSTRUMENTS IN THE WORLD AND NATIONAL ECONOMIES: THE PROBLEM OF THE CHOICE FOR UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The socio-economic mechanism for implementing international environmental agreements does not yet ensure the achievement of the goals set for them in the future. At the same time world and Ukrainian scholarly literature still lacks systematic research on the positive and negative impact of various financial and environmental instruments on the incipience of a «green» economy in the countries of the world.The negative financial and environmental instruments in the leading countries of the world are primarily attributed to as the so-called carbon tax which is the price of emissions into the air of every ton of carbon dioxide. The problem for Ukraine is its low level which does not encourage domestic business to introduce modern environmental technologies of production and involvement to our country predominantly «dirty» foreign investments.Ukrainian manufacturers need to take into account the fact that more and more enterprises in the leading countries of the world use such a new financial and environmental tool as the «internal price for carbon» which permits to take maximum account of climatic constraints and risks while developing the company's development strategy for the future. In particular the EU countries are considering the implementation of special certificates which will be providedthe type of energy used to produce one or another product (service).The extremely difficult economic problem for Ukraine is the employ of «warm» credits and «green» tariff which is distributed in many countries of the world. The point is that the latter's rate in Ukraine substantially exceeds the rate for traditional energy producers in many countries of the world leading to the domination on the renewable energy market large enterprises. Therefore the state must develop appropriate organizational and economic measures regarding the proper conditions for entry into this market of small business and households.In general the article reveals the peculiarities of the use of negative and positive financial and environmental instruments used to build the «green» economy in the countries of the world and the possibilities of their application in Ukraine.
Keywords: financial and environmental instruments, carbon tax, «warm» credit, revolving credit, green tariff, green investments, green bonds